Unveiling spatiotemporal temperature distribution at the skin in contact with hot solid surfaces - Jinu Sudhakaran; Dongchan Lee; Jung Kyung Kim (Case Studies in Thermal Engineering)
The significance of understanding the complex temperature patterns and variations on skin during contact with hot solid surfaces has grown recently due to its implications for human safety, comfort, and healthcare. We developed a novel method to visualize the distribution of skin contact temperatures (TSC), a task that was previously hindered by concealed contact areas. Thermographic images of heated thin solid plates and regression analyses established between measured temperatures from both sides of the plates were used to reconstruct TSC maps. This approach accommodated plates made of indium tin oxide (ITO) glass, copper, and fabric along with porcine skin as a substitute for human skin. Human finger experiments with mildly heated ITO glass were conducted to bridge the gap between laboratory simulations and practical scenarios. Spatiotemporal mapping of TSC unveiled localized hotspots, spatial gradients, and dynamic changes, highlighting the thermal stimulus area as well as the onset, intensity, and duration of pain sensation. The surface temperatures and thermophysical characteristics of both bodies in contact determine these patterns. Fabric's pain onset lagged behind ITO glass and copper. These findings have broad implications from shaping thermal safety protocols to advancing thermal tactile sensing for applications encompassing human–robot interactions, haptics, and electronic skins.